2019
DOI: 10.1021/acs.orglett.9b02054
|View full text |Cite
|
Sign up to set email alerts
|

C–H Pyridonation of (Hetero-)Arenes by Pyridinium Radical Cations

Abstract: Pyridones are important heteroaromatic scaffolds found in natural products and pharmaceuticals and are, therefore, of major interest in organic synthetic chemistry. Here we report the first C–H pyridonation of unactivated (hetero-)­arenes, providing a methodology to directly access N-aryl-2- and 4-pyridones. Generation of pyridinium radical cations through single-electron reduction allows for the synthesis of pyridones on structurally complex molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 67 publications
1
23
0
1
Order By: Relevance
“…On the basis of their previous studies,R itter and coworkers later found that the use of N-trifloxypyridinium salts bearing chloride in the 2-or 4-position enables the installation of 2-and 4-pyridones on (hetero-)arenes through ao ne-pot, two-step procedure involving C À Hf unctionalization by the radical cation and subsequent hydrolysis. [99]…”
Section: Angewandte Chemiementioning
confidence: 99%
“…On the basis of their previous studies,R itter and coworkers later found that the use of N-trifloxypyridinium salts bearing chloride in the 2-or 4-position enables the installation of 2-and 4-pyridones on (hetero-)arenes through ao ne-pot, two-step procedure involving C À Hf unctionalization by the radical cation and subsequent hydrolysis. [99]…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Based on earlier work, Ritter subsequently developed a onepot, two-step, direct C-H pyridonation of (hetero-)arenes using chloropyridinium radical cations. 23 This approach enables an unprecedented net C-H functionalization of an arene with the nitrogen atom of a pyridone under mild conditions. Pyridones are challenging substrates because of their low nucleophilicity and ambidentate nature but oen appear in therapeutic molecules and in SAR studies.…”
Section: Pyridinium Saltsmentioning
confidence: 99%
“…Recently, Ritter and co-workers developed an interesting C-H pyridonation reaction which successfully coupled 2-or 4-pyridones to arenes (Scheme 29). 34 Photoredox catalysis generates chloropyridinium radical cations for coupling to arenes to furnish N-arylpyridones in excellent yields. Late-stage modification of natural compounds was also realized by this method.…”
Section: Review Synthesismentioning
confidence: 99%